Magnesium Sulfate and Hematoma Expansion: An Ancillary Analysis of the FAST-MAG Randomized Trial. Issue 5 (5th April 2022) - Naidech, Andrew M.; Shkirkova, Kristina; Villablanca, Juan Pablo; Sanossian, Nerses; Liebeskind, David S.; Sharma, Latisha; Eckstein, Mark; Stratton, Samuel; Conwit, Robin; Hamilton, Scott; Saver, Jeffrey L.; ,
Abstract : Background: Intracerebral hemorrhage (ICH) is the deadliest form of stroke. In observational studies, lower serum magnesium has been linked to more hematoma expansion (HE) and intracranial hemorrhage, implying that supplemental magnesium sulfate is a potential acute treatment for patients with ICH and could reduce HE. FAST-MAG (Field Administration of Stroke Therapy - Magnesium) was a clinical trial of magnesium sulfate started prehospital in patients with acute stroke within 2 hours of last known well enrolled. CT was not required prior to enrollment, and several hundred patients with acute ICH were enrolled. In this ancillary analysis, we assessed the effect of magnesium sulfate treatment upon HE in patients with acute ICH. Methods: We retrospectively analyzed data that were prospectively collected in the FAST-MAG study. Patients received intravenous magnesium sulfate or matched placebo within 2 hours of onset. We compared HE among patients allocated to intravenous magnesium sulfate or placebo with a Mann-Whitney U . We used the same method to compare neurological deficit severity (National Institutes of Health Stroke Scale) and global disability (modified Rankin Scale) at 3 months. Results: Among 268 patients with ICH meeting study entry criteria, mean 65.4±13/4 years, 33% were female, and 211 (79%) had a history of hypertension. Initial deficit severities were median (interquartile range) of 4 (3–5) on the Los Angeles Motor Scale in the field and National Institutes of Health Stroke Scale score of 16 (9.5–25.5) early after hospital arrival. Follow-up brain imaging was performed a median of 17.1 (11.3–22.7) hours after first scan. The magnesium and placebo groups did not statistically differ in hematoma volume on arrival, 10.1 (5.6–28.7) versus 12.4 (5.6–28.7) mL ( P =0.6), or HE, 2.0 (0.1–7.4) versus 1.5 (−0.2 to 8) mL ( P =0.5). There was no difference in functional outcomes (modified Rankin Scale score of 3–6), 59% versus 50% ( P =0.5). Conclusions: Magnesium sulfate did not reduce HE or improve functional outcomes at 90 days. A benefit for patients with initial hypomagnesemia was not addressed. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00059332.